Atypical Chest X-Ray Calcification in an Idiopathic Constrictive Pericarditis Case. (10th July 2013) - Coşkun, Uğur; Canbolat, İsmail Polat; Sinan, Ümit Yaşar; Bostan, Cem; Kılıçkesmez, Kadriye; Yıldız, Ahmet; Başkurt, Murat; Turhan Çağlar, Fatma Nihan; Hatemi, Alican; Yıldız, Cenk Eray; Cöhcen, Sadettin; Gürmen, Aziz Tevfik; et al.
Abstract : Constrictive pericarditis is an uncommon cause of heart failure. It is a clinical entity caused by thickening, fibrosis, and/or calcification of the pericardium. We present a 50-year-old female patient who was admitted to our institution with a 6-month history of progressive dyspnea on exertion, abdominal swelling, and lower extremity edema. Her chest X-ray revealed an oblique linear calcification in the cardiac silhouette. Transthoracic echocardiography revealed biatrial enlargement. Left ventricular size and systolic function were normal. Cardiac computed tomography revealed the pericardial thickening (>5 mm) and heavy calcification in left atrioventricular groove. Simultaneous right and left heart catheterization showed elevation and equalization of right-sided and left-sided diastolic filling pressures, with characteristic dip, and plateau. Pericardiectomy was performed which revealed a thick, fibrous, calcified, and densely adherent pericardium constricting the heart. The postoperative period was uneventful and was in NYHA functional class I after 3 months.